Effectiveness of colchicine among patients with COVID-19 infection: A randomized, open-labeled, clinical trial - Aryan Mohamadfatih Jalal; Sheelan Faroz Aref; Dashty Abbas Albustany (Indian Journal of Rheumatology)
Background and Objective: In November 2019, there were abundant cases of COVID-19 which first case was reported in Wuhan, China. Colchicine has an important role in inhibiting activation of NLRP3 inflammasome that predispose to decrease cytokine production. This study aimed to evaluate whether colchicine is effective in treatment of corona virus disease of 2019 (COVID-19) patients or not. Patients and Methods: A randomized, open-labeled, clinical trial of Colchicine for the treatment of COVID-19, allocated between May 8, and June 18, 2021. The colchicine tablet dosage was 0.5 mg twice daily for 14 days added to the standard treatment versus control group who receive standard treatment without colchicine, with the trial registration ID: NCT04867226. The study was conducted in Erbil city-Iraq with the endpoints being clinical, laboratory parameters and duration of hospitalization. Results: Eighty patients participated in the study. Fewer patients in the colchicine group had musculoskeletal symptoms (17.5%, P = 0.001) in comparison to the patients, who received control treatment. The serum ferritin level in most of patients who treated with colchicine returned to normal in contrast to the control group, whose serum ferritin level was still high (P = 0.041). Similarly, the average of C-reactive protein and D-dimer after treatment among the colchicine group participants was significantly lower than the control group, the P values were 0.011 and 0.043 consecutively. The colchicine group patients stayed for a shorter duration at the hospital (18.4 days) compared to the control group (24.24 days). P value was 0.009. In addition to that the response and cure rate were higher in the colchicine group (56%) in the comparison to control group (43.1%). Conclusion: The colchicine drug can be effective in treating patients with COVID-19 infection by improving musculoskeletal symptoms and inhibiting inflammatory biomarkers; it is also effective in reducing duration of hospitalization.